Analisis Vegetasi Pulau-Pulau Kecil di Kecamatan Sekotong, Kabupaten Lombok Barat, Nusa Tenggara Barat - Fahmi Hidayat; Nirmala Ayu Aryanti (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
The rise of tourism development has increased the exploitation of natural resources and the increasing pressure on the environment on small island groups in West Nusa Tenggara, some of which are Gili Nanggu, Gili Sudak, and Gili Tangkong. The lack of attention to natural resources environmental preservation of small islands that are vulnerable to environmental changes, the purpose of the study was to determine the structure, species abundance, and differences in vegetation conditions on these islands. The technique used in vegetation analysis was a purposive sampling method, with a sampling intensity of 5% of each island area. The data obtained in the form of frequency, density, dominance, diversity index, index of important values (IVI), index of evenness, and wealth index, as well as a comparison test. On these islands were found 22 plant species belong to 13 families. The diversity index (H’) of vegetation types in Gili Nanggu, Gili Sudak and Gili Tangkong showed low to moderate categories. Species richness (R1) show a low category. Evenness (E) shows high, medium to low. According to a different test, there was no significant difference between the vegetation conditions in Gili Nanggu, Gili Sudak and Gili Tangkong.